Studies on the effect of glass transition on the crystalline transition in syndiotactic polystyrene - solvent complexes - Naidu, Sudhakar; Ramesh, N. C. (Macromolecular Symposia, 2008)
Amorphous syndiotactic polystyrene (sPS) was crystallized at room temperature in Norbornadiene (bicyclo[2,2,1]-hepta-2,5-diene), Mesitylene (1,3,5-Trimethyl benzene), 3-Carene (3,7,7-trimethyl bicyclo[4,1,0]hept-3-ene) and DMN (1,4-Dimethylnaphthalene) to form the sPS-solvent complex (h form) with respective solvent molecules. In situ HTFTIR studies showed that the delta form to gamma form transformation temperature occurs well below the glass transition temperature of sPS, which is depressed due to the presence of solvent in the amorphous phase; higher the solvent content in the complex, lower the transition temperature. Glass transition temperatures determined by Modulated differential scanning calorimetry (MDSC) coincide with the transition temperatures, indicating that the delta form transforms into gamma form at the glass transition temperature for these complexes. Such a behavior is very different from the behaviour of the sPS- solvent complexes formed by dichloromethane, chloroform, toluene, o-dichlorobenzene, decalin (cis-trans) etc. and for these complexes the transition occur well above the T(g).
Keywords: Crystallization; glass transition; infrared spectroscopy; Syndiotactic polystyrene